Measuring Attitude and Skill Based Program Outcomes - Issues and Solution - Loni, Deepali Yoginath; Admuthe, L. S. (Journal of Engineering Education Transformations, 2017)
Considering the transformation that is happening in the education system, the changing global focus and their demands to have ready employable students, has made the education system to adopt new tools and techniques to enhance student learning and develop professional attitude in them. Incorporating Outcome Based Education (OBE) is a way to achieve this. The paper focuses on various practical issues in implementation of OBE concerned with the structure of engineering curriculum. The paper has revealed the considerable gap in the curriculum structure for the attainment of the attitude and skill based outcomes.An implemented solution to these issues is presented and its execution is discussed in detail. Rubric is the most suitable assessment tool for the measuring these outcomes. The various concerns in the design of rubrics are also identified and clarified with sample rubrics.